Altered temporal stability in dynamic neural networks underlies connectivity changes in neurodevelopment - Brookes, Matthew J.; Groom, Madeleine J.; Liuzzi, Lucrezia; Hill, Ryan M.; Smith, Helen J.F.; Briley, Paul M.; Hall, Emma L.; Hunt, Benjamin A.E.; Gascoyne, Lauren E.; Taylor, Margot J.; Liddle, Peter F.; Morris, Peter G.; et al. (Elsevier, 2018)
Network connectivity is an integral feature of human brain function, and characterising its maturational trajectory is a critical step towards understanding healthy and atypical neurodevelopment. Here, we used magnetoencephalography (MEG) to investigate both stationary (i.e. time averaged) and rapidly modulating (dynamic) electrophysiological connectivity, in participants aged from mid-childhood to early adulthood (youngest participant 9 years old; oldest participant 25 years old). Stationary functional connectivity (measured via inter-regional coordination of neural oscillations) increased with age in the alpha and beta frequency bands, particularly in bilateral parietal and temporo-parietal connections. Our dynamic analysis (also applied to alpha/beta oscillations) revealed the spatiotemporal signatures of 8 dynamic networks; these modulate on a ∼100 ms time scale, and temporal stability in attentional networks was found to increase with age. Significant overlap was found between age-modulated dynamic networks and inter-regional oscillatory coordination, implying that altered network dynamics underlie age related changes in functional connectivity. Our results provide novel insights into brain network electrophysiology, and lay a foundation for future work in childhood disorders.